An Ecdotic Approach to Lorenzo Varela’s Poetry Editions - García López, José Ángel (Madrygal. Revista de Estudios Gallegos, 2015)
The object of this essay is to contribute to the establishment of the poetic works of Lorenzo Varela (Havana, 1916 - Madrid, 1978) with a little textual critical analysis. Writer of premature vocation, Varela soon extended the frame of Spanish Literature to enrich Literature in the Galician language.